PELAKSANAAN MUSRENBANG DAERAH DALAM PROSES PERENCANAAN DAN PENGANGGARAN PARTISIPATIF - Murni Rahayu Purwaningsih (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
A decentralized government system tends to prioritize a bottom-up and participatory approach. Musrenbang is a forum to embody community participation in regional and national development. In its implementation, community participation tends to be a formality and only a requirement in the planning and budgeting process. This paper aims to identify participatory planning and budgeting in implementing regional musrenbang and provide recommendations based on literature and previous studies for more effective and participatory musrenbang. This paper uses a descriptive qualitative method with secondary data sources. This paper analyzes a case study of the implementation of the Musrenbang RKPD that was conducted in three regions with different levels and referred to the eight stages of Conyers' participation. The results show that, in general, community participation in the regional musrenbang was included in stage 5 of Conyers' participation (placation); namely, the power holder allowed the community to provide input, but the decision-making process remained in the hands of the power holder. Participation is defined as attendance and how the government can respond to the public. The role of planners needs to be strengthened by enabling planners to mediate and negotiate with the power to find win-win solutions from stakeholders.